Design of an advanced intelligent instrument with waveform recognition based on the ITMS platform. (25th January 2010) - De Arcas, G.; Vega, J.; Murari, A.; Nieto, J.; Lopez, J.M.; Ruiz, M.; Barrera, E.; Ratta, G.A.
Searching for similar behaviours in previous data plays a key role in fusion research, but it can be quite challenging to implement from a practical point of view. This paper describes the design of an intelligent measurement instrument that uses Similar Waveform Recognition Systems (SWRS) to extract knowledge from the signals it acquires. The system is perceived as an ethernet measurement instrument that permits acquisition of several waveforms simultaneously and identification of similar behaviours by searching in previous data using distributed SWRS. The implementation is another example of the advantages that local processing capabilities can provide in Data Acquisition (DAQ) applications.